ANALISIS KEBUTUHAN TERHADAP MEDIA AUGMENTED REALITY PADA MATERI KLASIFIKASI HEWAN UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA PESERTA DIDIK FASE D - Adis Sherly; Saleh Hidayat; Bagas Rasid Sidik (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
This study aims to analyze the needs of students for Augmented Reality (AR) based learning media on animal classification material to improve critical thinking skills. The background of this research is based on the difficulty of students in understanding abstract concepts in classification material, such as distinguishing morphological and physiological characteristics between animal groups, as well as the lack of visual media that support learning. This research used descriptive qualitative method with data collection techniques through questionnaires, interviews, observations, and literature studies. The results showed that teachers and students of SMP Pusri Palembang had never used AR media in learning, but showed high enthusiasm for its use. Learners considered AR as an interesting media and able to help them understand the concept of animal classification in a concrete and fun way. Teachers also acknowledge that AR can be an innovative solution to overcome student learning difficulties and support the strengthening of character and 21st century skills. These findings indicate that the development of AR media in science learning is needed and is in line with the principles of the Merdeka Curriculum which emphasizes contextual and meaningful learning. Hopefully, the results of this study can serve as a basis for developing more adaptive and effective technology-based learning media in the future.